Nilai Karakter pada Cerpen Senyum Karyamin Karya Ahmad Tohari: Pendekatan Sosiologi Sastra - Hanah, Ayu; Falasifah, Fiqtin (Perkumpulan Pengelola Jurnal Bahasa dan Sastra Indonesia serta Pengajarannya, 2023)
The purpose of this research is to determine the character values contained in the short story â€œSenyum Karyaminâ€ by Ahmad Tohari. The research method used is a qualitative study with descriptive analysis method. The approach used is the sociology of literature approach. The short story